2001
DOI: 10.1097/00000374-200103000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Altered Emotional Perception in Alcoholics: Deficits in Affective Prosody Comprehension

Abstract: Alcoholics and FAexp subjects were significantly less accurate at APC compared with controls. These alcohol-exposed subjects appear to be deficient in the ability to understand emotional valence in the speech of others, which results in errors of judgment that may impair social interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 27 publications
3
41
0
3
Order By: Relevance
“…Most studies aiming at identifying the sources of social difficulties in AD individuals have focused on difficulties in emotional processing. For example, it has been shown that AD individuals have difficulties recognizing emotion expressions (especially anger) from faces (Kornreich et al, 2003;Maurage et al, 2011), postures (Maurage et al, 2009), or voice prosody (Monnot et al, 2001).…”
mentioning
confidence: 99%
“…Most studies aiming at identifying the sources of social difficulties in AD individuals have focused on difficulties in emotional processing. For example, it has been shown that AD individuals have difficulties recognizing emotion expressions (especially anger) from faces (Kornreich et al, 2003;Maurage et al, 2011), postures (Maurage et al, 2009), or voice prosody (Monnot et al, 2001).…”
mentioning
confidence: 99%
“…Researchers have noted overlaps between the pragmatic impairments associated with RHD and those seen in people with autistic spectrum disorders (Ellis & Gunter, 1999;Ozonoff & Miller, 1996), schizophrenia (Mitchell & Crow, 2005), semantic-pragmatic disorder (Shields, 1991), traumatic brain injury (Martin & McDonald, 2003 (Cherney & Canter, 1993), alcoholism (Monnot, Nixon, Lovallo, & Ross, 2001), as well as in healthy elderly people (Kjelgaard, Titone, & Wingfield, 1999).…”
Section: Pragmatics Rhd and Other Clinical Groupsmentioning
confidence: 99%
“…19,20 The Aprosodia Battery (ApB) has been used as an effective research tool in various clinical populations. 21,[36][37][38][39] For details concerning the rational, administration, acoustic measurements and scoring of the ApB see reference 15 and the Appendix. Affective-prosodic production includes tasks of Spontaneous production and Repetition involving Word, Monosyllabic, and Asyllabic stimuli.…”
Section: Testing Proceduresmentioning
confidence: 99%